2001
DOI: 10.1080/09541440042000025
|View full text |Cite
|
Sign up to set email alerts
|

Does audiovisual speech perception use information about facial configuration?

Abstract: The McGurk illusion eVectively demonstrates the audiovisual nature of speech perception. When an auditory syllable is dubbed onto an incongruous visual syllable the resulting percept is usually not either of the components, but their combination or fusion. The present experiment investigated the persistence of the McGurk eVect when the facial con guration context of the audiovisual stimuli was manipulated. Two congruent and two incongruent audiovisual syllables were created from spoken /ipi/ and /iki/. These a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
3
10
1
Order By: Relevance
“…However, research into face and speech perception has challenged this notion, demonstrating that configural distortions to the face can degrade its efficacy for supporting visual speech detection (Hietanen et al, 2001;Rosenblum et al, 2000). The results of the current research seem to be more consistent with these latter studies, suggesting that affect may also interact with speech.…”
Section: Dynamic Interactions Of Speech and Affectsupporting
confidence: 72%
See 2 more Smart Citations
“…However, research into face and speech perception has challenged this notion, demonstrating that configural distortions to the face can degrade its efficacy for supporting visual speech detection (Hietanen et al, 2001;Rosenblum et al, 2000). The results of the current research seem to be more consistent with these latter studies, suggesting that affect may also interact with speech.…”
Section: Dynamic Interactions Of Speech and Affectsupporting
confidence: 72%
“…While the affective expressions clearly influenced performance, the large configural distortions created by visual manipulations had little influence on audiovisual speech detection, only doing so inasmuch as they interacted with the affective displays. Hence, while previous research demonstrated that some methods of scrambling faces can influence audiovisual syllable detection (Hietanen et al, 2001;Rosenblum et al, 2000), in the current experiments, with full-length sentences, perceivers were found to suffer little audiovisual speech decrement, if any, from our more subtle configural distortions. The facial chimeras are unusual in configuration in that they are perfectly symmetrical, and despite efforts to maintain a centralized head position for the actor, minor head shifts were normal (thus producing small changes in the head size of her image).…”
Section: Facial Configuration and Emotionmentioning
confidence: 70%
See 1 more Smart Citation
“…It was, however, not face inversion in itself that was responsible for diminishing the McGurk effect but rather the inversion of the lips, which would result in a loss of configural coherence between the articulatory movements and the auditory signal (Rosenblum, Yakel & Green, 2000). Hietanen, Manninen, Sams and Surakka (2001) confirmed that, provided lips are presented upright, a normal face configuration was not necessary for a McGurk illusion to occur. They found that only an asymmetrically scrambled face stimulus (both eyes, mouth, and noise being horizontally and vertically displaced) produced strong deterioration.…”
supporting
confidence: 56%
“…Crucially, these procedures manipulated only subjectspecific cognitive variables (Engel et al, 2001), without ever changing the bottom-up input signal (i.e., the auditory or the visual component of the McGurk stimuli, as, e.g., in MacDonald et al, 2000), the immediate sensory context (as in Green & Gerdeman, 1995;Hietanen, Manninen, Sams, & Surakka, 2001;Walker et al, 1995), or the attentional weighting of the auditory vs. visual input signals (as in Massaro & Warner, 1977;Summerfield & McGrath, 1984).…”
mentioning
confidence: 99%